Whither an International Issue: The Columbia River Treaty, the Canada/US Border, and the Curious Case of Libby, MT. Issue 5 (19th October 2020) - Hundley, James M.
ABSTRACT: International borders are an integral component of multilevel governance theorizing in other parts of the world, mainly Europe. This is seldom the focus for theorizing or explicating events and relationships at North American borders. This is particularly clear at the Canada/US border where local jurisdictions are often excluded from international discussions. This article examines the efforts of one Montana legislator to gain compensation for losses incurred under the Columbia River Treaty and the creation of the binational Lake Koocanusa reservoir. The Treaty established a series of dams to control seasonal flooding and provide inexpensive hydropower. September 16, 2014 was the 50-year anniversary of the Treaty and first possible date by which either country could give notice to withdraw; neither party wants to withdraw but both are interested in renegotiating certain components. This article argues that the Treaty shifts between being viewed as a domestic and international issue obscuring the role of the local. Scholars need to employ multilevel governance and the concept of the region in our theorizing of borders to incorporate local level actors in what is largely an international political domain. Understanding how power operates at and through the border, at these various scales, necessitates including relevant local actors.